Suling Dewa dalam upacara Ngaponin Suku Sasak - Muhammad Arsyad (Institut Seni Indonesia Yogyakarta, 2017)
Suling Dewa is a very distinctive art and became the identity of Sasak Lombok Ethnic. This art stores a variety of uniqueness and that is you can’t found in other areas, one of which is the interval of the tone and the lyrics are so contrasting. This art consists only of two players a vocalist and one flute players. In each of the elements in theSuling Dewa Sasak have the meaning of soul from the mirroring of Sasaknese ethnic identity. This distinctive art in its existence in society is widely used in various sacred rituals and ceremonies. One of Suling Dewa functions is used in Ngaponin ceremony or clean up the old metal ceremony every four years. In Ngaponin ceremony series there is one mandatory procession called as Mendewa. The fungtions of Mendewa procession is called the metaphysical object for making the energy wall of guard. Islam Metu Telu is a belief system in Lombok society. This belief system the majority people life in north of Lombok island and the minority you can find that in all areas of Lombok Island. A beautiful combination pattern is contained in the teachings of Islam Metu Telu or also known as Wetu Telu and WaktuTelu. The combination in question is a pattern of syncretism between religions and cultures that are so harmony that so maintained by society. The presentation of Suling Dewa in Ngaponin ceremony consists of two aspects, the textual and contextual. The textual aspect consists of musical events such as gending, music instrument, lyrics of vocal mantra, instrumental organology and contextual aspects including non-musical events consisting of time, place and other ceremonial processions. Suling Dewa to this day is a primary item in a ceremony or a specific ritual that uses Suling Dewa. Any ceremonies and rituals that use Suling Dewa can’t be done without the presence of the Suling Dewa artist. This proves give the concluses the Suling Dewa have a important position in the life of Sasak Kuto - kute community. Keywords: Suling Dewa, Ngaponin, Islam Metu Telu